The Legality of Cryptocurrency Transactions in Indonesia - Alum Simbolon; Desy Indriani Grace Sinaga (Jurnal Daulat Hukum, 2022)
This study aims to know the cryptocurrency is a digital currency that is used as a medium for transactions or payments between people online (peer to peer). Cryptocurrencyis a virtual currency that is protected with a secret code that is complex enough to protect and maintain the security of the value of the currency. Several types of cryptocurrencies include ethereum, ripple, litecoin, dogecoin, mrai, dashcoin, and so on. Currently, cryptocurrency is an investment instrument that is quite attractive to the public, the popularity of crypto investment itself can be seen from the increasing number of cryptocurrency investors. Therefore,The Commodity Futures Trading Supervisory Agency (CoFTRA) of the Ministry of Trade as a regulator that oversees cryptocurrencies in Indonesia has begun to tighten supervision of crypto asset trading. The research used is normative legal research with a statutory and conceptual approach. The research stages were carried out by analyzing the Commodity Futures Trading Supervisory Agency Regulation Number 7 of 2020 concerning the Determination of the List of Crypto Assets that can be Traded in the Crypto Asset Physical Market (PerCoFTRA Number 7 of 2020), and Act No. 7 of 2011 concerning Currencies, to find out cryptocurrency legality in Indonesia. The protection carried out on crypto assets is by first registering the type of cryptocurrency with CoFTRA to be analyzed and determined to be tradable or not. The determination of tradable crypto assets is carried out through the Analytical Hierarchy Process (AHP) valuation method which has several assessment criteria that must be met, where the conditions for crypto assets that can be traded on the physical asset market must be guided by CoFTRA No. 7 of 2020.